Antidepressant Use During Early Pregnancy and the Risk of Congenital Anomalies. Issue 7 (6th June 2013) - Vasilakis‐Scaramozza, Catherine; Aschengrau, Ann; Cabral, Howard; Jick, Susan S.
<x xml:space="preserve">Abstract</x> Study Objective To estimate and compare the prevalence of congenital anomalies among the offspring of women exposed and not exposed to antidepressants during early pregnancy. Design Matched cohort study. Data Source United Kingdom's General Practice Research Database. Subjects Women exposed to tricyclic and selective serotonin reuptake inhibitor (SSRI) antidepressants during the first trimester of pregnancy (3276 women) and a sample of women matched in a 2:1 ratio who had no exposure to any antidepressant during the first trimester of pregnancy (6617 women). Measurements and Main Results The prevalence of any congenital anomaly was 31.0 (95% confidence interval [CI] 27.0–35.5) per 1000 pregnancies among women not exposed to antidepressants and 27.2 (95% CI 22.1–33.4) per 1000 pregnancies among women exposed to antidepressants. The relative risk of having a child with an anomaly in mothers who were exposed to tricyclics and SSRIs during the first trimester compared with mothers not exposed to these drugs was 0.9 (95% CI 0.7–1.1). The relative risks for any anomaly among women exposed to antidepressants were 0.9 (95% CI 0.6–1.2) for tricylics and 0.9 (95% CI 0.7–1.2) for SSRIs. We found no statistically significant, stable increases in the risk of specific anomaly subtypes among women exposed to these antidepressants; however, the number of exposed cases was small. Conclusion Exposure to tricyclics and SSRIs during the first trimester of pregnancy was not associated with a statistically significant increased risk of congenital anomalies in the offspring of mothers exposed to these drugs.